2022
DOI: 10.1101/2022.02.03.478955
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic rearrangements of mobile genetic elements associated with carbapenem resistance of Acinetobacter baumannii

Abstract: With the excessive genome plasticity, Acinetobacter baumannii has the capability to acquire and disseminate antimicrobial resistance genes that are often associated with mobile genetic elements (MGE). Analyzing the genetic environment of resistance genes often provides valuable information on the origin, emergence, evolution and spread of resistance. Thus, we characterized the genomic features of some clinical isolates of carbapenem-resistant A. baumannii to understand the role of diverse MGE and their genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…The ARG and virulence mobile elements identified here appear to be scattered among IC2 A. baumannii, as observed in several other genomes in the current dataset and also reported in IC2 genomes from India [31] and China [32]. In addition, virulence and conjugative plasmids have also been reported in other ICs, such as IC5 and IC7, in Bolivia [33], a country that borders Brazil.…”
Section: Discussionsupporting
confidence: 84%
“…The ARG and virulence mobile elements identified here appear to be scattered among IC2 A. baumannii, as observed in several other genomes in the current dataset and also reported in IC2 genomes from India [31] and China [32]. In addition, virulence and conjugative plasmids have also been reported in other ICs, such as IC5 and IC7, in Bolivia [33], a country that borders Brazil.…”
Section: Discussionsupporting
confidence: 84%
“…Several studies have demonstrated horizontal gene transfer of mobile antimicrobial-resistant genetic elements (known as mobile gene element MEG) to and from A. baumannii through plasmids, integrons, insertion sequences, transposons, prophages, etc. [35][36][37][38]. K. pneumoniae is one of the most wellstudied bacteria, known as a main pool of drug resistance and as a transporter of resistance genes among Gram-negative bacteria, including A. baumannii [37,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38]. K. pneumoniae is one of the most wellstudied bacteria, known as a main pool of drug resistance and as a transporter of resistance genes among Gram-negative bacteria, including A. baumannii [37,39,40]. In a recent study published by Kore ň et al, a whole-genome sequencing of CR strains of K. pneumoniae, isolated from the Bratislava University Hospital complex, was performed [41,42].…”
Section: Discussionmentioning
confidence: 99%